Antimicrobial Peptides: Their Role in Innate Immune System and Usage in Future Drug Development - Tristia Rinanda (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Antimicrobial peptides naturally play a role in the innate  immune system of any living organisms. These small  molecules are known as "ancient weapon" and also  recognized as natural antibiotics. Antimicrobial  peptides  have  distinct  characteristics  including  their  unique  structures  which  are strongly  correlated  to  their  antimicrobial  activities.  Recently  the  development  of  antimicrobial peptides as future antimicrobial agents has become a major issue in the pharmaceutical business. This  article  will  discuss  the  natural  role  of  antimicrobial  peptides  in  host  defence  system  and  the relationship of their structure with antimicrobial activity. This article will also discuss the challenge in developing antimicrobial peptides as future antimicrobial agents.